Description of Five Essential Elements towards Online Cooperative Learning in English for Nursing Students - Sofyan, Wini Fitrina; Agustini, Aat; Wati, Eti (Inspiring: English Education Journal, 2024)
Cooperative Learning (CL) develops many essential elements, including positive interdependence, individual accountability, social skills, group processing and face-to-face interaction among students in their respective groups. In connection with this question, this study aims to describe the appearance of five essential elements in Online-Cooperative-Learning (OCL). This research is a quantitative descriptive study, where a Likert scale questionnaire investigates the occurrence of the five basic elements of OCL among 109 samples of nursing students who have participated in OCL in English for Specific Purposes (ESP). This study employs univariate analysis, describing the percentage occurrence of these five OCL elements. The univariate analysis results show that these five essential elements of CL significantly appeared in online learning. Positive interdependence in OCL groups appeared at 83%, interpersonal competence successfully emerged in OCL at 85%, individual accountability emerged at 83%, and OCL group processing appeared at 84%, shaping students to adapt to "critical" conditions. Meanwhile, face-to-face promotive interaction at 76% formed positive strong bonds within the group to overcome challenges that arose during online learning. These findings indicate that OCL can provide access to building the five basic elements of CL, making OCL highly relevant for use in ESP learning for nursing students.